The Effect of Skimming Method to Improve Students’ Ability in Reading Comprehension on Narrative Text. - Bobby Pramjit Singh Dhillon; Herman Herman; Syafryadin Syafryadin (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2020)
This research deals with the effect of using skimming method in teaching reading comprehension smk negeri 2 pematangsiantar on narrative text. The problem of this research are “what is the students’ ability in reading without using skimming method at Grade XI students’ of SMK N.2 Pematangsiantar. What is the students’ ability in reading by using skimming method at Grade XI students’ of SMK N.2”. The purpose of this research are to find out the students’ ability in reading without using skimming method at grade XI students in SMK N 2 Pematangsiantar on reading narrative text, to find out the the students ability in reading by using skimming method to the skill of grade XI students in SMK N 2 Pematangsiantar on reading narrative text. To answer the problem the researchers uses theories: Micklukey and Jefferies (2007), Grellet (2000), Milter (2001), Jhon and Dara (2005), David Nunan (1991), Douglas Newton (2000), Douglas Brown (2003), Rae Pica (2000), Roger Brown (1973), Ronald Carter (1998), Scoot Thornburry (2002), Wilga Rivers (1987), Diane Larsen (1990), Judi Willis (2008), Jack and Theodore (1986). The research design is a quantitative research. As an experimental research, it aims to know the effect of the technique that given and apply whether it influences to the object or no. In this research in collecting the data the researcher has to do three steps, they are pre-test, treatment, post-test. The researchers find out that the effect of using skimming method can increase the students’ skill in reading of narrative text. It can be proven from the test of students’ score in posttest of experimental class which the treatment the researchers did the treatment by using skimming method. By using skimming method, the students can increase their ability in reading of narrative text.